Pengaruh Penggunaan Media Sosial dan Pelatihan Kerja Terhadap Kinerja Pegawai dengan Kompensasi Sebagai Mediasi pada Badan Keuangan Daerah Kabupaten Pacitan - Alien Dewi Alifah; Ahmad Mardalis (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The purpose of this study was to analyze the effect of Social Media Use and Job Training on Employee Performance with Compensation as a mediator at the Regional Financial Agency of Pacitan Regency. The population of this study were all employees of the regional financial agency of Pacitan Regency with a sample used in this study of 101 respondents adjusted to the probability sampling technique by purposive sampling. This study is a quantitative study using data sources, namely primary data obtained through interviews, observations, and measurements using questionnaires conducted directly by researchers. The analysis tool used is SmartPLS. The results of this study indicate that the conclusions in this study are 1.) there is a positive and significant effect of social media use on employee performance, while there is a negative and insignificant effect of social media use on compensation 2.) there is a positive and significant effect of job training on employee performance and compensation variables 3.) compensation has a significant positive effect on employee performance 4.) the use of social media and job training can be mediated by compensation and affect employee performance